TETRAHYDROPYRROLOTHIAZINE COMPOUNDS - WATSON BRIAN MORGAN; GREEN STEVEN JAMES; WINNEROSKI JR. LEONARD LARRY; MERGOTT DUSTIN JAMES (2015)
본 발명은 하기 화학식 I의 화합물 또는 그의 제약상 허용되는 염을 제공한다. <화학식 I>상기 식에서, R은 H 또는 F이고; A는 하기 (A), (B), (C) 또는 (D)이다. The present invention provides a compound of Formula I: wherein R is H or F; and A is: or a pharmaceutically acceptable salt thereof.